Hubungan Body Image dan Penyesuaian Diri dengan Kemampuan Kolaborasi pada Siswa - Dwi Yuwono Puji Sugiharto; Fenti Ameliana (Ma'soem University, 2021)
Collaboration skills is one of the competencies in 21st century skills that are very important in life, especially for the younger generation to develop themselves in learning as well as prepare their competencies to become a competitive workforce in the global era. This study aims to determine the relationship between body image, self-adjustment, and collaboration ability. This study uses a quantitative approach with ex post facto methods and correlational design. The results showed (1) There was no relationship between body image and the collaboration ability of SMA Karangturi Semarang students (p>0.01, =0.055) (2) There was a positive and significant relationship between self-adjustment and collaboration skills of SMA Karangturi Semarang students ( p<0.01, =0.646 (3) There is a positive relationship between body image and self-adjustment with the collaboration ability of SMA Karangturi Semarang students with (p>0.01, R=0.658; F=0.433). So it can be concluded that body image has no effect on collaboration ability. Then the higher the student's self-adjustment ability, the higher the collaboration ability. In addition, simultaneously the body image and self-adjustment variables have a positive influence on students' collaboration abilities, so the higher the student's body image and self-adjustment, the higher their collaboration abilities.